The (Inter)cultural Missing Link in Conference Interpreting - Leal Lobato, Ana l. (HERMES - Journal of Language and Communication in Business, 2019)
The second half of the twentieth century brought about increased international contacts between people from different origins, which led to changes in the translation studies landscape, impacting conference interpreters as well. Although interpreting scholars acknowledge that interpreters are both linguistic and intercultural mediators, at first glance, culture and intercultural mediation appear to be neglected in the domain of conference interpreting, unlike the domains of community and sign language interpreting. In this paper, I conduct an analysis on how the established professional discourse and the scholarly literature have portrayed culture and intercultural mediation in conference interpreting. The analysis reveals various conceptualizations of culture and different stances regarding intercultural mediation. Amongst them, reductionist conceptualizations of culture seem to dominate; conceptualizations that have informed the conference interpreting pedagogy. However, this state of affairs contrasts sharply with the current culturally diverse interpreting landscape, what might have an impact on practice and professional identity.